PP.76 Use of Ultrasound in Management of Obesity in Pregnancy – Current Practise in the West of Scotland. (26th April 2013) - Wu, P; McMillan, M; Moss, H; Gibson, JL
Abstract : For a 3-month period, a prospective audit of management of obesity in pregnancy was undertaken in Glasgow and Clyde maternity hospitals. Two hundred and fourteen women were identified out of a total of 3, 834 deliveries during the study period: 76 (36%) had a booking body mass index (BMI) ≥40 and 138 (64%) had a BMI of 35–39. One hundred and ninety-nine women (93%) underwent fetal structural scan to screen for anomalies. Out of these, 168 (84%) had it performed at recommended time period of 18–20+6 weeks' gestation. Twenty-five (13%) women had their structural scan between 21–24 weeks. One hundred and forty-one women (66%) had a complete structural scan at first visit, and the remainder were offered repeat scan. Fifty-five (28%) women returned for rescan and 44 (22%) women had a complete structural survey then. The assessment of fetal growth was performed in 170 (79%) women, with 43 (20%), 42 (20%) and 59 (28%) of women having had 1, 2 or 3 growth scans. Twenty-six (12%) women had more than 3 scans. At the first growth scan, only 17 (10%) women had a macrosomic fetus with an abdominal circumference (AC) > 95 th centile, while 5 (3%) had a fetal AC < 5 th centile. One hundred and three (48%) women were delivered by Caesarean sections, and 47 of these were performed as emergency surgeries. In conclusion, there is scope for improvement in sonographic surveillance of these high risk pregnancies. The effective use of sonographic resources may be best achieved by a planned ultrasound schedule.